2008
DOI: 10.1111/j.1742-4658.2008.06519.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of an anti‐oxidative stress mechanism of quetiapine

Abstract: Quetiapine is an atypical antipsychotic drug (APD) for the treatment of symptoms in patients with schizophrenia. This drug effectively alleviates positive and negative symptoms as well as cognitive impairment [1][2][3]. In addition, quetiapine is well tolerated and causes the lowest incidence of extra-pyramidal symptoms [1,4] We have shown that quetiapine, a new antipsychotic drug, protects cultured cells against oxidative stress-related cytotoxicities induced by amyloid b (Ab)25-35, and that quetiapine preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 54 publications
4
17
0
Order By: Relevance
“…QUE at higher doses has a significant antioxidant effect. Similar data were demonstrated by Xu et al [37] . They showed that QUE protects cultured cells against oxidative stress-related cytotoxicities induced by amyloid-␤ by blocking hydroxyl radical generation induced by amyloid.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…QUE at higher doses has a significant antioxidant effect. Similar data were demonstrated by Xu et al [37] . They showed that QUE protects cultured cells against oxidative stress-related cytotoxicities induced by amyloid-␤ by blocking hydroxyl radical generation induced by amyloid.…”
Section: Discussionsupporting
confidence: 81%
“…They showed that QUE protects cultured cells against oxidative stress-related cytotoxicities induced by amyloid-␤ by blocking hydroxyl radical generation induced by amyloid. QUE by eliminating hydroxyl radical attenuates oxidative stress thus protecting brain cells against oxidative-stress-related damage and improving cognitive function in patients with schizophrenia [37] . The antioxidant mechanism of QUE may contribute to the low incidence of EPS and movement disorders caused by this drug in patients with schizophrenia, and may be effective in treating TD caused by other antipsychotics [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Ab [25][26][27][28][29][30][31][32][33][34][35] , the most toxic peptide fragment derived from the amyloid precursor protein, was dissolved in deionized distilled water at a concentration of 1 mM, and was incubated in a 37°C for 72 h to induce maximal aggregation according to the previous report [39]. The solution was stored at -80°C to create stable conditions for the aged stock solution, and diluted in serum-free medium to desired concentrations immediately before use.…”
Section: Preparation Of Ab 25-35 Stock Solutionmentioning
confidence: 99%
“…Previous studies have provided evidence for the protection of mitochondrial function in ameliorating synaptic changes and the consequent cognitive impairments in AD animal models. A representative example of the many mitochondria-protecting approaches is the application of antioxidants to human AD, AD animal and cell models, which demonstrates significant amelioration of mitochondrial/neuronal dysfunction against Ab toxicity (28,31,74,90). More recent studies suggested the striking efficacy of mitochondria-targeting antioxidants including MitoQ, SS peptides, and MitoE in strengthening mitochondria in their respiration, membrane potential, and calcium-handling capacity from toxic insults including the Ab (45,53,78).…”
Section: Fig 6 Working Hypothesismentioning
confidence: 99%